Optimizing the spatial pattern of the cold island to mitigate the urban heat island effect - Qiu, Jiang; Li, Xiaoyu; Qian, Wenqi (Ecological indicators, 2023)
[Display omitted] •Construct a cold island connectivity framework: cooling source area-cooling network.•Identify cooling sources by morphological spatial pattern analysis and connectivity.•Utilizes the Minimal Cumulative Resistance to construct the cooling network.•The UHI effect is alleviated by optimizing the spatial pattern of cold islands. Numerous studies on reducing the urban heat island effect have concentrated on isolated cold islands, analyzing their cooling impact in terms of size and shape. From an international perspective, studies have shown that enhancing the connectivity of cold islands can enhance the cooling effect of cold islands, but they do not suggest specific processes and ideas for cold island connectivity. This study aims to investigate how to connect cold islands to optimize the spatial pattern of the cold island. Therefore, a cold island connectivity framework is constructed in this study: cooling source area - cooling network. Firstly, the core area of the cold island was identified by the morphological spatial pattern analysis. Then, connectivity analysis was applied to identify the cooling sources. Afterward, a minimum cumulative resistance model is used to construct the cooling network. In Nanjing, for case in point, the results reveal that a total of 27 cooling source areas and 52 cooling corridors have been identified. 6 first-level CSAs situated in the northern suburbs of Nanjing prevent the spread of the urban heat island effect. 2 second-level CSAs and 18 third-level CSAs are scattered throughout Nanjing to improve the urban climate. The 29 primary corridors help to mitigate heat transfer from the city center. The 23 secondary corridors are mainly located in urban centers contributing to preventing heat island from aggregating. The framework can be used as a strategic measure to prevent the fragmentation and isolation of the cold island, which provides implications for preventing the further expansion of urban heat island.